2012
DOI: 10.1039/c2cc36559f
|View full text |Cite
|
Sign up to set email alerts
|

A one-step homogeneous plasmonic circular dichroism detection of aqueous mercury ions using nucleic acid functionalized gold nanorods

Abstract: In this work, we report the application of gold nanorods ladder assemblies as chiroptical sensors for detecting mercury ions (Hg(2+)). By taking advantage of the Hg(2+)-mediated T-T base pair of DNA and the high sensitivity of CD measurements, the method offers a simple and sensitive detection of target Hg(2+) residues in water. Therefore, the developed method will be a promising tool for monitoring heavy metal ions, other small molecules and biomacromolecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

5
5

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 28 publications
1
71
0
Order By: Relevance
“…These instrumental methods have great stability and reliability; however, expensive instrumentation and complicated sample preparation procedures are also required. Since Ono found that thymine-thymine (T-T) mismatches are very selective for Hg 2+ binding (Miyake et al, 2006), several methods for the detection of Hg 2+ have been developed based on small molecule fluorophores (Al-Kady, Gaber, Hussein, & Ebeid, 2009;Chen et al, 2008;He, Zhao, He, Liu, Duan, 2008), polymers (Liu et al, 2007), oligonucleotides (Chiang et al, 2008;Liu, Hsieh, Huang, Lin, & Chang, 2008;Ono & Togashi, 2004;Zhu et al, 2012), proteins (Guo & Irudayaraj, 2011;Wen, Deng, Guo, & Dong, 2011) and metal nanoparticles (Sun et al, 2010). These fluorimetric, colorimetric and electrochemical sensors not only have some advantages but also have disadvantages, as they are complicated, costly and time consuming.…”
Section: Mercury-dna Interaction Based Detection Of Mercury Ions By Dmentioning
confidence: 99%
“…These instrumental methods have great stability and reliability; however, expensive instrumentation and complicated sample preparation procedures are also required. Since Ono found that thymine-thymine (T-T) mismatches are very selective for Hg 2+ binding (Miyake et al, 2006), several methods for the detection of Hg 2+ have been developed based on small molecule fluorophores (Al-Kady, Gaber, Hussein, & Ebeid, 2009;Chen et al, 2008;He, Zhao, He, Liu, Duan, 2008), polymers (Liu et al, 2007), oligonucleotides (Chiang et al, 2008;Liu, Hsieh, Huang, Lin, & Chang, 2008;Ono & Togashi, 2004;Zhu et al, 2012), proteins (Guo & Irudayaraj, 2011;Wen, Deng, Guo, & Dong, 2011) and metal nanoparticles (Sun et al, 2010). These fluorimetric, colorimetric and electrochemical sensors not only have some advantages but also have disadvantages, as they are complicated, costly and time consuming.…”
Section: Mercury-dna Interaction Based Detection Of Mercury Ions By Dmentioning
confidence: 99%
“…Although these sensors are highly sensitive and selective, most of them can only be used for single-ion (Hg 2+ or Ag + ) detection. [ 3,21,[24][25][26][27] As Hg 2+ and Ag + usually coexist in the environment and both of them are of potential hazards, it is highly desirable to create an assay for the simultaneous detection of these ions.…”
Section: Triple Raman Label-encoded Gold Nanoparticle Trimers For Simmentioning
confidence: 99%
“…The post optimization aptamers possess more advantages than antibodies such as chemical synthesis, easy modification, target versatility, high stability and resistance to degradation and denaturation. Moreover, biosensors with various aptamers based on nanomaterials (Guo et al, 2007;Kwon et al, 2010;Wu et al, 2009), which may potentially be designed for a lower concentration of biomolecules, have attracted wide attention (Ma et al, 2014;Zhu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%